Pharmacological correction of the hemostasis system for the surgical treatment of bitches with tumours of the mammary gland - D. D. Bely; M. V. Rublenko; S. V. Rublenko; I. D. Yevtushenko; N. I. Suslova; V. V. Samoyuluk (Regulatory Mechanisms in Biosystems, 2018)
We carried out the clinical validation of pathogenetically substantiated protocols for the treatment of female dogs with tumour lesions of the mammary gland. The positive effect of corrective therapy was characterized by a decrease in the physiological level of fibrinogen: in benign tumours in 10 days, malignant – in 14 days against the background of its stable high level in control animals with malignant neoplasia. In the postoperative period in experimental animals, the functioning of the internal coagulation unit was restored, as evidenced by the normalization of the activated partial thromboplastin time for benign tumours by days 10–14, malignant – by 14 days. In control patients, these changes were detected only for benign neoplasms. Shifts of the external mechanism of blood coagulation in the experimental groups were eliminated in benign neoplasia cases in 10 days, malignant cases in 14 days against the background of severe disorders in this link in control patients throughout the observation period. The positive effect of complex treatment regimens is confirmed by the restoration of total fibrinolytic activity by days 10–14 due to the normalization in the same terms of the plasminogen activator and tissue plasminogen activator by days 3–7. In control animals, the total fibrinolytic activity was consistent with those of clinically healthy animals only for benign neoplasms. The balancing of coagulation and fibrinolytic mechanisms was accompanied by a decrease in the activity of proteolytic inhibitors: α2-macroglobulin in experimental groups with benign neoplasia by day 10, malignant – by days 10–14, and control – respectively, by days 3 and 14; α1-proteinase inhibitor in all groups by day 3. Concentration of nitric oxide after extirpation of benign tumors already at day 3 of the postoperative period in all groups corresponded to the indexes of clinically healthy dogs, with the removal of malignant tumours – in experimental animals at day 3, control – at day 14. The content of malondialdehyde and ceruloplasmin against the background of pharmacological correction was restored by days 10–14, whereas in control animals – only with benign neoplasms by day 14. Postoperative pharmacological correction of the hemostasis system can significantly improve the results of treatment in cancer patients.